2010
DOI: 10.1186/ar3016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental stress in inflammatory rheumatic diseases: a review of psychophysiological stress responses

Abstract: IntroductionStressful events are thought to contribute to the aetiology, maintenance and exacerbation of rheumatic diseases. Given the growing interest in acute stress responses and disease, this review investigates the impact of real-life experimental psychosocial, cognitive, exercise and sensory stressors on autonomic, neuroendocrine and immune function in patients with inflammatory rheumatic diseases.MethodsDatabases Medline, PsychINFO, Embase, Cinahl and Pubmed were screened for studies (1985 to 2009) inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 100 publications
(366 reference statements)
3
45
1
2
Order By: Relevance
“…2) nervous system (ANS), which includes the sympathoadrenal medullary (SAM) axis that secretes adrenaline and noradrenaline, and the neuroendocrine system, which includes the hypothalamicepituitaryeadrenal (HPA) axis that secretes cortisol, a major stress regulatory parameter. Because both pathways are connected with the immune system, influencing these pathways through psychological factors may influence disease processes in immune-mediated rheumatic diseases [23,26,27]. …”
Section: Risk and Resilience Factors For Quality Of Life And Disease mentioning
confidence: 99%
See 2 more Smart Citations
“…2) nervous system (ANS), which includes the sympathoadrenal medullary (SAM) axis that secretes adrenaline and noradrenaline, and the neuroendocrine system, which includes the hypothalamicepituitaryeadrenal (HPA) axis that secretes cortisol, a major stress regulatory parameter. Because both pathways are connected with the immune system, influencing these pathways through psychological factors may influence disease processes in immune-mediated rheumatic diseases [23,26,27]. …”
Section: Risk and Resilience Factors For Quality Of Life And Disease mentioning
confidence: 99%
“…However, causality cannot be ascertained as prospective associations could also be due to factors that are associated with both the risk or resilience factor and the change in quality of life or disease impact. Although the laboratory setting is not a natural environment, which may limit the generalizability of the findings to daily life settings, experimental studies that manipulate a psychological factor and examine its effect on functioning while controlling other key factors enable true causal conclusions [26]. Although not all psychological factors can (easily) be manipulated (e.g., personality characteristics) and not much experimental research has been conducted in patients with inflammatory rheumatic diseases, the following paragraphs will provide the current knowledge base in this or related fields (e.g., pain stimulation in healthy participants or other chronic pain populations).…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in psychoneuroimmunology have provided insight into the complex mechanisms by which stressors might affect the homeostasis and the body's immune system (de Brouwer et al, 2010). Stress challenges the organism's homeostatic mechanisms, triggering a cascade of events that should, normally, maintain or allow a return to equilibrium (Pêgo et al, 2010).…”
mentioning
confidence: 99%
“…It was shown that psychological stress is also thought to contribute to the aetiology, maintenance and exacerbation of rheumatic diseases (de Brouwer et al, 2010). Stress has been studied in several autoimmune rheumatic diseases, including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA) (Cutolo & Straub, 2006).…”
mentioning
confidence: 99%